1997
DOI: 10.1159/000121188
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Model: Change in the Posterior Fossa with Surgically Induced Spina bif ida aperta in Mouse

Abstract: On the basis of experimental studies on mouse embryos in which spina bifida development of the brain ventricular system. Mouse embryos were exposed and surgically treated at gestation day 12 to produce spina bifida aperta, and operated embryos were cultured exo utero in the peritoneal cavity of the pregnant dam. Embryos were harvested at gestation day 14. Open neural tube defects resulted in 7 out of 10 embryos surviving surgery. Histological examination revealed that the sizes of ventricles in both the supra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…The studies outlined in this review have focused on a variety of animals: large mammals such as sheep [14], pigs [15]and primates [16], small mammals such as the mouse [17], rat [15, 18]and rabbit [19, 20], and avian species such as the White Peking duck [21]and chick embryos [22, 23, 24]. Larger mammals, such as the sheep and monkey, carry on average one embryo per pregnancy and typically tolerate surgical manipulations well, but are expensive and have long gestations (145 and 165 days, respectively).…”
Section: Surgical Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies outlined in this review have focused on a variety of animals: large mammals such as sheep [14], pigs [15]and primates [16], small mammals such as the mouse [17], rat [15, 18]and rabbit [19, 20], and avian species such as the White Peking duck [21]and chick embryos [22, 23, 24]. Larger mammals, such as the sheep and monkey, carry on average one embryo per pregnancy and typically tolerate surgical manipulations well, but are expensive and have long gestations (145 and 165 days, respectively).…”
Section: Surgical Animal Modelsmentioning
confidence: 99%
“…These factors reduce the number of experiments that can be performed in a given time frame. Most small experimental animals are multiparous, which allows for experimentation on large numbers of embryos, ranging from 3 to 10 embryos per pregnancy and have short gestational periods of 3–4 weeks [17, 19, 20, 21, 25]. The drawbacks are the difficulties with manipulation of the uterus and subsequent survival of the embryo.…”
Section: Surgical Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…McLone and Knepper (1989) showed that there was a decrease in all of the vesicular volumes of splotch mice with open neural tubes. More recently, Inagaki et al (1997) demonstrated a decrease in size of the ventricles in both the supra-and infratentorial regions in mouse embryos after surgical introduction of spina bifida aperta. They concluded that leakage of CSF through the neural tube opening results in a decrease in intraventricular fluid pressure that leads to Chiari II type malformations.…”
mentioning
confidence: 99%
“…When the hindbrains of living chick embryos were intubated with a small glass capillary tube for 24 hr, allowing the release of intraluminal pressure, their brains had 50% less tissue and number of cells compared to control embryos of identical ages (Desmond and Jacobson, 1977;Desmond, 1985). Recently, Inagaki et al (1997) demonstrated a decrease in size of the posterior fossa of intubated mice embryos in utero as well.…”
mentioning
confidence: 99%